Uji Aktivitas Formulasi Mikrokapsul Ekstrak Etanol Kunyit Putih (Curcuma zedoaria Rosc) Sebagai Antidislipedemia terhadapTikus Putih (Rattus Norvegicus) - Kevin Wijaya; Razoki Razoki; Roy Indrianto Bangar (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Elevated blood cholesterol levels are known to be a major risk factor for cardiovascular disease. Hypercholesterolemia can trigger atherosclerosis, which in turn increases the risk of coronary heart disease and stroke. One approach to managing cholesterol levels is through the use of natural ingredients with antihyperlipidemic activity. White turmeric (Curcuma zedoaria Rosc) is an herbal plant long used in traditional medicine and contains bioactive compounds such as curcuminoids and essential oils. These compounds are reported to have antioxidant and anti-inflammatory activities, as well as potential as agents for lowering blood lipid levels. Herbal-based therapies are increasingly considered as safe alternatives to synthetic drugs in managing hyperlipidemia. This study aims to evaluate the effectiveness of a microencapsulated preparation of white turmeric ethanol extract in reducing total cholesterol levels in male rats (Rattus norvegicus) induced by a high-fat diet. The study was conducted experimentally using 25 rats divided into six treatment groups. The groups consisted of normal controls, negative controls, positive controls using simvastatin, and three treatment groups given white turmeric extract microcapsules at concentrations of 0.25%, 0.50%, and 0.75%. The microencapsulation technique was applied to improve the stability and bioavailability of the turmeric extract. Cholesterol levels were measured before and after treatment. The results showed that the treatment group with the 0.25% concentration produced the most significant cholesterol reduction, from 110 mg/dL to 59 mg/dL. These findings indicate that even at a relatively low concentration, microencapsulated turmeric extract can significantly reduce cholesterol levels in vivo. Therefore, it can be concluded that white turmeric extract in microcapsule form is effective in lowering total cholesterol levels, especially at the 0.25% dose. This suggests that Curcuma zedoaria microcapsules hold promise as a natural therapeutic option for managing hypercholesterolemia and reducing cardiovascular risk.